Delayed Identification of Treatment Failure causes High Levels of Acquired Drug Resistance and Less Future Drug Options among HIV-1-infected South Indians. - Sathasivam Sivamalar; Selvamurthi Gomathi; Jayaseelan Boobalan; Pachamuthu Balakrishnan; Amrose Pradeep; Chithra A Devaraj; Sunil Suhas Solomon; Duraisamy Nallusamy; Varalakshmi Sureka; Shanmugam Saravanan (Journal of Coastal Life Medicine, 2023)
Objective: This study aims to investigate the prevalence of HIV-1 drug resistance mutations (DRMs) in individuals experiencing immunological failure (IF) while on first-line regimens based on nucleoside reverse transcriptase inhibitors (NRTIs), namely thymidine analogues (TAs) such as AZT and D4T, as well as non-thymidine analogues (NTAs) like TDF. The objective is to assess the viral drug susceptibility in order to inform the selection of optimal second-line therapeutic alternatives. Methods Cross-sectional study comprised 300 people with HIV-1 infection who were on first-line HAART. The HIV-1 pol gene, which spans 20–240 RT codons, was genotyped using IAS-USA 2014 and the Stanford HIV drug resistance database v7.0. Results: In total 300 Participant receiving first-line therapy was included. Majority of the TDF failures were on EFV based first-line (89% vs 45%) (p <0.0001), level of resistance for TDF and AZT shows, that resistance to TDF was about one-third (37%) of TDF participants and onefourth (23%) of AZT participants; resistance to AZT was 17% among TDF participants and 47% among AZT participants; resistance to both AZT and TDF was significantly high among AZT participants [21% vs. 8%, OR 3.057 (95% CI 1.4-6.8), p < 0.0001]. Conclusion: Acquired drug resistance were induced by delayed diagnosis of treatment failure. Therefore, we must take steps to regularize virological monitoring with integrated resistance testing in LMIC (Low and Middle Income Countries), such as India; this will help to preserve the effectiveness of ARV and assure the success of eradicating AIDS as a public health concern by 2030.